HBV Drug Resistance Substitutions Existed before the Clinical Approval of Nucleos(t)ide Analogues: A Bioinformatic Analysis by GenBank Data Mining - Xizhan Xu; Kuanhui Xiang; Mingze Su; Li, Yao; Wei Ji; Yutang Li; Hui Zhuang; Li, Tong (Viruses, 2017)
Naturally occurring nucleos(t)ide analogue resistance (NUCr) substitution frequencies in the reverse transcriptase (RT) of the hepatitis B virus (HBV) were studied extensively after the clinical approval of nucleos(t)ide analogues (NUCs; year of approval 1998). We aimed to study NUCr substitutions in HBV RT sequences obtained before 1998 and better understand the evolution of RT sequences without NUC pressures. Our strategy was to retrieve HBV sequences from GenBank deposited before 1998. The initial search used the keywords "hepatitis B virus" or "HBV" and 1139 sequences were found. Data analyses included information extraction: sequence quality control and amino acid substitution analysis on 8 primary NUCr and 3 secondary substitution codons. Three hundred and ninety-four RT-containing sequences of 8 genotypes from 25 countries in 4 continents were selected. Twenty-seven (6.9%) sequences were found to harbor substitutions at NUCr-related codons. Secondary substitutions (rtL80V and rtV173G/A/L) occurred more frequently than primary NUCr substitutions (rtI169L; rtA181G; T184A/S; rtS202T/R; rtM204L and rtM250K). Typical amino acid substitutions associated with NUCr were of rtL80V, rtV173L and rtT184A/S. We confirm the presence of naturally occurring typical HBV NUCr substitutions with very low frequencies, and secondary substitutions are more likely to occur than primary NUCr substitutions without the selective pressure of NUCs. Keywords: hepatitis B virus; naturally occurring; nucleos(t)ides analogue resistance; pre-existing; reverse transcriptase; substitution.